Advancing computational biophysics with Virtual Reality - Afonso Bernardino da Silva Pinto (2020)
Computational models are powerful tools for exploring the properties of complex biological systems. In computational neuroscience, allowing easy computational exploration and visualization of this models is crucial for the progress of the field. In recent years, Virtual Reality hardware and visualization systems have become more affordable and this opens a window of opportunity for visualization services. The current major problem of 3D visualization concerns usability (i.e., navigation and selection). During this dissertation, we will hypothesize that the replacement of 3D for VR will (1) overcome the usability issues mentioned and eventually (2) boost user effectiveness regarding field of study (neuroscience) concerns. In order to evaluate the results of the work developed under this dissertation, a two-part experiment will be carried out where a group of individuals must perform a set of predetermined tasks and evaluate their experience using 3D in the first and VR in the last part. Besides the self-evaluation of the experiment, data such as completion time and task correctness will also be used to quantify the effectiveness of the visualization method. Given the aforementioned experiment, a prototype of a (web-based) application with Virtual Reality visualization shall be developed. The 3D visualization will be provided by a web-based open-sourced framework called Geppetto. Each of the decisions made in the development of the prototype will be properly analyzed in this document, as well as the scientific literature that will serve as a basis when necessary. Besides the study of Virtual Reality itself, standard methods with respect to the visualization of (neuro)scientific information will also be analyzed. The proposed solution will seek to constitute a solid and sufficiently generic work base to be applied, not only in the scope of neuroscience, but also in several other contexts where visualization through VR might be successful.